Unconditional and Conditional Wage Polarization in Europe - Paolo Naticchioni; Giuseppe Ragusa; Riccardo Massari (Institute for the Study of Labor (IZA), 2014)
This paper investigates the dynamics of the distribution of unconditional and conditional - on technology - wages in Europe, using both industry and individual level data for the period 1995-2007. We find that the unconditional wage distribution shows scant signs of polarization in Europe. On the other hand, the effect of technology is more nuanced. At the industry level, technological changes have an effect on polarization of jobs, but not on polarization of wages. At the individual level, we use a counterfactual distributional analysis which accounts for the heterogeneity of tasks across occupations, and we find only mild evidence of wage polarization. Technology affects the lower and upper part of the wage distribution in different ways, with service tasks affecting the lower quantiles and abstract tasks affecting the higher ones.
Keywords: J3; J5; 330; wage inequality; polarization; occupational tasks; offshoring; RIF-regressions